5x+23=2(11x+27)

Simple and best practice solution for 5x+23=2(11x+27) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+23=2(11x+27) equation:


Simplifying
5x + 23 = 2(11x + 27)

Reorder the terms:
23 + 5x = 2(11x + 27)

Reorder the terms:
23 + 5x = 2(27 + 11x)
23 + 5x = (27 * 2 + 11x * 2)
23 + 5x = (54 + 22x)

Solving
23 + 5x = 54 + 22x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22x' to each side of the equation.
23 + 5x + -22x = 54 + 22x + -22x

Combine like terms: 5x + -22x = -17x
23 + -17x = 54 + 22x + -22x

Combine like terms: 22x + -22x = 0
23 + -17x = 54 + 0
23 + -17x = 54

Add '-23' to each side of the equation.
23 + -23 + -17x = 54 + -23

Combine like terms: 23 + -23 = 0
0 + -17x = 54 + -23
-17x = 54 + -23

Combine like terms: 54 + -23 = 31
-17x = 31

Divide each side by '-17'.
x = -1.823529412

Simplifying
x = -1.823529412

See similar equations:

| 11x^2+5x-18=0 | | X+5=1x | | 60n=45 | | 18x+8y=60whatisy | | 8x=666 | | 5x+5y=-40 | | (3w-4)(7+w)=0 | | 6y+15=39 | | 5n=3n+14 | | 8x+13y=-74 | | 6x-(2x+1)=1 | | 3x+13=8x+48 | | (x+5)-2(4-3x)=2(x+3)-4 | | 7c-63=22c-72 | | 1100-x=550 | | x*2+y*2=49 | | 2x^2+24x+50=0 | | (z+9)(3z+4)=0 | | 2b+7=4b+2 | | 15+4x=6+7x | | -2(-b-4)=-(b-8) | | 8.7x+4.42=-11.3x+3.18 | | 6+4w=13+3w | | -8(x+7)+5=-51 | | 4r+6=13+2r | | x*2+4*x+y*2-21=0 | | ln(4x^6+2x^3)=y | | 180=120x | | -2(b-4)=-(b-8) | | x^2+1-11=0 | | 4xn+2=10+2n | | 20w^2+10w+40=0 |

Equations solver categories